Strategi Perang Informasi (Netwar) dan Perjuangan Non-violent dalam Upaya Pemisahan Diri Papua di Indonesia - Rany Purnama Hadi (Department of International Relations, Brawijaya University, 2017)
This paper analyzed the development of West Papua secession movement from guerrilla struggle to nonviolent struggle through the use of information technology. Since 2000s until 2016, West Papua movement mostly dominated by online campaign as an attempt to struggle for independence. Using theory and concept about nonviolent struggle and netwar the author found that information technology which is internet, utilized by West Papua movement as strategy to campaign and spread West Papua struggle for independent against Indonesian government in international level. By the use of online media and social network, West Papua movement influence international society to give support and sympathy to their struggle. This online strategy then creates cyberspace as a battle field of opinion between West Papua movement and Indonesian government.Keywords: West Papua resistance, Non-violent struggle, Netwar, Online campaign, Information warfare